Evaluation of Blood Markers at Admission for Predicting Community Acquired Pneumonia in Chronic Obstructive Pulmonary Disease. (3rd September 2021) - Gao, Shupei; Duan, Yifei; Chen, Jinqing; Wang, Jianmiao
Abstract: Acute exacerbations of Chronic Obstructive Pulmonary Disease (AECOPD) and community acquired pneumonia (CAP) are two common acute attacks in COPD patients and it is not always easy to determine whether a COPD patient at admission has parenchymal infection or bronchial infection. Comprehensive comparison between AECOPD patients and CAP patients with COPD (COPD + CAP) can help us understand them better. We retrospectively collected the medical records of AECOPD and COPD + CAP patients. Systemic inflammation, eosinophilic inflammation, damage to other organs, common chronic comorbidities, structural changes, phenotype and endotype distributions and coagulation functions between two groups were compared and correlations of these characteristics in total subjects, AECOPD patients and COPD + CAP patients were analyzed. Logistic regression analysis was performed to select helpful biomarkers for distinguishing between them. Receiver operator characteristic (ROC) curve was plotted to assess the diagnostic value of selected biomarkers and their combination. A nomogram was established for the differential diagnosis of AECOPD and COPD + CAP. A total of 206 patients were included into our analysis. In these subjects, 104 patients were classified as AECOPD group and 102 patients were considered to have COPD + CAP mainly based on their chest CT scan results. The counts of eosinophils (EOS), basophils (BAS) and lymphocytes (LYM) and percentage of total white blood cell count, hemoglobin and hematocrit were increased in AECOPD patients compared with COPD + CAP patients. The counts of neutrophils (NEU) and percentage of total white blood cell count, C-reactive protein (CRP), Erythrocyte sedimentation rate (ESR), fibrinogen, D-dimer and N-Terminal pro-brain natriuretic peptide (NT-proBNP) levels were increased in COPD + CAP patients. After logistic regression analysis, EOS < 0.5 × 10 9 /L, ESR ≥ 8 mm/H and NT-proBNP ≥ 100 pg/mL were selected as helpful biomarkers for diagnosis of COPD + CAP instead of AECOPD. Area under the ROC curve (AUC) of the combination of selected biomarkers was 0.764(0.698-0.829). A nomogram was established and the calibration curve suggested that fitting efficiency of the nomogram was good. AECOPD and COPD + CAP are markedly different, mainly reflected in eosinophilic inflammation, systemic inflammation and coagulation function. Correlations between some common inflammatory biomarkers are also different in the two groups. A nomogram was established to offer help to clinicians for differential diagnosis of these two diseases.